Platelet Abnormalities in Muscular Dystrophy - Yarom, R; Meyer, S; More, R; Liebergall, M; Eldor, A (Thrombosis and Haemostasis, 1983)
Platelets which have complex membranes and calcium shifts similar to those in muscles were investigated in 14 patients with muscular dystrophy and 20 suitable controls. In 4 Duchenne and one limb-girdle dystrophy aggregations were done and found to be depressed with adrenaline and ADP. Electron microscopic and chemical examinations revealed an increased number of dense bodies, changed permeability and/or binding of cations and elevated intracellular calcium in all the 9 cases of Duchenne dystrophy while the 2 limb-girdle and 3 myotonic dystrophies varied.A two phase polymer separation system applied to fixed platelets of all patients and controls showed no abnormality of surface negative charge.
Keywords: Platelet calcium; Adrenaline aggregation; Surface-charge